Development of a seat for electric vehicles in tropical megacities - Muhammad Sufyan Zainalabidin. (2013)
With increasing global fuel economy standards and new legislation in reducing carbon dioxide ( ) emission into the atmosphere, an electric taxi was the focus of this project so as to replace gasoline-powered vehicles. Electric vehicles are considered greener than that of gasoline ones. To further improve the efficiency and mileage of the electric vehicle, the author was tasked to design the rear seat structure out of Carbon-Fibre-Reinforced-Plastic, CFRP. CFRP is a lightweight material which provides more strength and stiffness as compared to steel. Also, this report shows the development of building an integrated child booster seat.